Moldova : Country Procurement Assessment Report (CPAR) - World Bank (World Bank, 2012)
Moldova is one of the poorest countries in Europe. It is landlocked, bounded by Ukraine on the east and Romania on the west. Like many other former Soviet Republics, Moldova has experienced economic difficulties. Since its economy was highly dependent on the rest of the Soviet Union for energy and raw materials, the breakdown in trade following the breakup of the Soviet Union had severe impacts, exacerbated by drought and civil conflict. Moldova has made progress in economic reform since independence. The Government liberalized most prices, phased out subsidies, and privatized housing, government enterprises, agricultural state land, and other state-owned assets. However, as of early 2010, Moldova's economy has been in recession. The main sources of growth in previous years, remittances, imports, and foreign investment, were undermined by the global crisis, resulting in weaker domestic and external demand, fiscal imbalances, limited financial intermediation, and an increase in the level of poverty.